Using Short-Form Videos to Get Clinical Trial Newcomers to Sign Up: Message-Testing Experiment - Sisi Hu; Ciera E Kirkpatrick; Namyeon Lee; Yoorim Hong; Sungkyoung Lee; Amanda Hinnant (JMIR Publications, 2024)
BackgroundRecruiting participants for clinical trials poses challenges. Major barriers to participation include psychological factors (eg, fear and mistrust) and logistical constraints (eg, transportation, cost, and scheduling). The strategic design of clinical trial messaging can help overcome these barriers. While strategic communication can be done through various channels (eg, recruitment advertisements), health care providers on the internet have been found to be key sources for communicating clinical trial information to US adults in the social media era. ObjectiveThis study aims to examine how communication source (ie, medical doctors and peers) and message framing of TikTok videos (ie, psychological and logistical framing) influence clinical trial-related attitudes, perceptions, and sign-up behaviors under the guidance of the integrated behavioral model. MethodsThis study used a 2 (source: doctor vs peer) × 2 (framing: psychological vs logistical) between-participant factorial design web-based experiment targeting adults in the United States who had never participated in clinical trials (ie, newcomers). A Qualtrics panel was used to recruit and compensate the study respondents (n=561). Participants viewed short-form videos with doctors or peers, using psychological or logistical framing. The main outcome measures included perceived source credibility, self-efficacy, attitude toward clinical trial participation, behavioral intention, and sign-up behavior. Structural equation modeling was used to analyze the direct and indirect effects of message factors on the outcome variables. Source (doctor=1; peer=0) and framing (psychological=1; logistical=0) were dummy-coded. ResultsDoctor-featured messages led to greater perceived source credibility (β=.31, P<.001), leading to greater self-efficacy (95% CI 0.13-0.30), which in turn enhanced behavioral intention (95% CI 0.12-0.29) and clinical trial sign-up behavior (95% CI 0.02-0.04). Logistical barrier-framed messages led to greater self-efficacy (β=-.09, P=.02), resulting in higher intention to participate in clinical trials (95% CI -0.38 to -0.03) and improved sign-up behavior (95% CI -0.06 to -0.004). Logistical barrier-framed messages were also directly associated with an increased likelihood of signing up for a clinical trial (β=-.08, P=.03). The model accounted for 21% of the variance in clinical trial sign-up behavior. Attitude did not significantly affect behavioral intention in this study (β=.08, P=.14), and psychological and logistical barrier-framed messages did not significantly differ in attitudes toward clinical trial participation (β=-.04, P=.09). ConclusionsThese findings advance our understanding of how people process popular message characteristics in short-form videos and lend practical guidance for communicators. We encourage medical professionals to consider short-form video sites (eg, TikTok and Instagram Reels) as effective tools for discussing clinical trials and participation opportunities. Specifically, featuring doctors discussing efforts to reduce logistical barriers is recommended. Our measuring of actual behavior as an outcome is a rare and noteworthy contribution to this research.